Strategi Non-Governmental Organization (NGO) Jikalahari dalam Tata Kelola Hutan Provinsi Riau Terkait Upaya Pengendalian Perubahan Iklim Global Tahun 2013-2023 - Rustianur Zaky Zahran, Alfajri (Journal of Diplomacy and International Studies, 2023)
Effective forest governance plays a crucial role in global climate change control efforts. Poor forest governance contributes to the increasing occurrence of climate change disaster such as floods, wildfires, and haze. Riau is one of the province in Indonesia that facing various forest governance issues, ranging from flawed spatial planning regulation (RTRW), mere conceptualization of the Riau Hijau plan, to numerous court cases that involving forest and land fires (Karhutla) that implicate certain corporate entities. This research discusses the strategies employed by the NGO Jikalahari in forest governance in Riau Province for global climate change control efforts. The research adopts a qualitative descriptive approach, using semi-structured interviews as the primary data collection technique, while literature review is used to obtain secondary data. The research applies the green theory perspective and John McCormick environmental NGO strategy concept. The finding of this research indicate that NGO Jikalahari has successfully implemented nine of the environmental NGO strategies proposed by John McCormick, thus namely: 1) Working with Elected Officials, Bureaucrats, and Employees of Corporation; 2) Raising and Spending Money; 3) Campaigning and Organizing Public Protests; 4) Promoting Media Coverage of Environmental Issues; 5) Litigation and Monitoring the Implementation of Environmental Law; 6) Information Exchange; 7) Undertaking Research; 8) Acquiring and Managing Property; 9) Generating Local Community Involvement in Environmnetal Protection. Additionally, NGO Jikalahari has significantly contributed to forest governance in Riau Province in the context of global climate change control.